Consumption of Ayahuasca by children and pregnant women: medical controversies and religious perspectives - Labate, Beatriz Caiuby (Journal of psychoactive drugs, 2011)
In 2010, the Brazilian Government agency responsible for drug-related issues formulated official Resolutions that categorized the consumption of ayahuasca by pregnant women and children in the Santo Daime and União do Vegetal ayahuasca-based religions as an “exercise of parental rights.” Although ayahuasca groups do enjoy a relative degree of social legitimacy and formal legal recognition in Brazil, the participation of pregnant women and children nevertheless continues to provoke heated discussion. This article raises the main issues involved in the public debate over this subject. In the first part, a diverse group of biomedical and health specialists was consulted, and their opinions were briefly analyzed. In the second, a full interview with a follower of one branch of Santo Daime, mother of four children who took ayahuasca during all her pregnancies, and whose children all drink ayahuasca, is presented. Her interview reveals important cultural parameters of ayahuasca consumption. The article explores common themes and contradictions found between the biomedical, anthropological, and ayahuasca-users' discourses. It raises central issues regarding the limits of freedom of religion and the state's right to interfere in family matters. The following analysis also has implications regarding the role of science in influencing policy decisions on drug use.
Gesehen am 12.07.2022